A professional learning model supporting teachers to integrate digital technologies - Sheffield, Rachel; Blackley, Susan; Moro, P. (Western Australian Institute for Educational Research Inc, 2018)
Â© 2018, Western Australian Institute for Educational Research Inc. All rights reserved. Contemporary teachers have an obligation to support and scaffold studentsâ€™ learning in digital technologies and to do this in authentic contexts. In order for teachers to be successful in this, their own competency in digital technologies needs to be high, and their own 21st century learning skills of communication, collaboration, creativity and problem solving need to be well honed. Teachers are challenged to understand not only the associated digital pedagogical practices and content knowledge, but also to be familiar with how the technology components can be best used to support learning (Ertmer & Ottenbreit-Leftwich, 2013). This paper reports on a 2016 pilot project that incorporated the key components of highly effective teacher professional learning to leverage transformational change: on-site, over-time, through a community of practice and building the confidence and competence of teachers to implement the digital technologies curriculum (Jimoyiannis, 2010; Rodrigues, 2005; Wenger, White & Smith, 2009). This project supported 28 primary and secondary school teachers from regional Western Australia to collaborate through a distributed digital learning network or a guided Professional Learning Network that was called a â€œclusterâ€? to develop and reflect upon their digital capabilities.